PUBLIC PARTICIPATION IN THE DECISION OF NATIONAL ENERGY REGULATOR OF SOUTH AFRICA ON ELECTRICITY TARIFFS - Debeila, Mokiritle Billy (My University, 2012)
The extent of public influence in the decisions that government and government agencies take is an issue of contentious discussion. There are varying views on the importance of public participation in decision-making in state institutions and public policy. There are those who support a soft approach to public participation while others believe that the public must be fully engaged and should contribute meaningfully to the decision-making process. It is not yet clear whether public participation processes in South Africa are influencing decision-making and policy direction. There appears to be more emphasis on conducting public participation with a purpose to comply to legislative requirements instead of the public participation enhancing the quality of the decisions that are taken by the public officials. NERSA conducts public participation prior to taking decisions on the price of electricity. People participating in these public participations hold a view that NERSA does not consider their submissions when taking decisions on electricity tariffs. This view is created by the public‟s perception that NERSA seems to take decisions contrary to what the public has advised them on. The main objective of this research was to determine whether public inputs have any influence in the decisions that NERSA takes regarding electricity tariff increases. The overall finding in the study showed that NERSA does handle all public comments and inputs fairly and with great thought. The process of gaining public input was found to be fair but not effective. It was discovered that the general public does not influence NERSA decisions to a great extent .It was also established that the government departments and other key industry stakeholders influenced NERSA but not as much as initially thought. NERSA employees were the main people who influence decisions that the Regulator takes.
MM thesis - P&DM
Keywords: Electricity tariffs; National electricity regulator of South Africa; Public participation; Government decision-making